African animal trypanocide resistance: A systematic review and meta-analysis - Kasozi, Keneth Iceland; MacLeod, Ewan Thomas; Welburn, Susan Christina (Frontiers in Veterinary Science, 2023)
Background: African Animal trypanocide resistance (AATr) continues to undermine global efforts to eliminate transmission of African trypanosomiasis in endemic communities. The continued lack of new trypanocides has precipitated drug misuse and overuse thus contributing to the devel-opment of the AATr phenotype. In this study, we investigated the threat associated with AATr by using the major globally available chemotherapeutical agents. Methods: A total of 7 electronic databases were screened for article on trypanocide resistance in AATr by using keywords on preclinical and clinical trials with number of animals with treatment relapse, and days taken to relapse, and resistant gene markers using the PRIMSA checklist. Data was cleaned using the SR deduplicator, covidence and analyzed using Cochrane RevMan®. Dichotomous outputs were presented using risk ratio (RR) while continuous data was presented using the standardized mean difference (SMD) at 95% confidence interval. Results: A total of 8 publications in which diminazene aceturate (DA), isometamidium chloride (ISM) and homidium chloride/bromide (HB)were iden-tified as the major trypanocides used. In all preclinical studies, development of resistance was in the order of HB > ISM > DA. DA vs ISM (SMD =0.15, 95% CI: -0.54, 0.83; I2 = 46%, P =0.05)., DA vs HB (SMD = 0.96, 95% CI: 0.47, 1.45; I2 = 0%, P = 0.86)., HB VS ISM (SMD = -0.41, 95% CI: -0.96, 0.14; I2 =5%, P =0.38) showing multiple cross resistance. Clinical studies also showed evidence of multi-drug resistance on DA and ISM (RR = 1.01, 95% CI: 0.71-1.43; I2 = 46%, P = 0.16). To address resistance most preclinical studies increased the dosage and the treatment time, and this failed to improve on the patient prognosis. Major markers of resistance explored include: TbAT1, P1/P2 transporters and folate transporters F-I, F-II, F-III and polyamine biosynthesis inhibitors. In addition, immuno-suppressed hosts favors development of AATr. Conclusion: AATr is a threat which requires a shift in the current disease control strategies in most developing nations due to inter-species trans-mission. Multi drug cross resistance against the only accessible trypanocides is a major public health risk justifying the need to revise policy in developing countries.